The Effects of Thoracic Epidural Analgesia on Postoperative Pain and Myocardial Protection in Coronary Artery Bypass Surgery - Bestami Barış Çelik; Türkan Kudsioğlu; Nehir Tandoğar (Haseki Tıp Bülteni, 2015)
Aim: Thoracic epidural analgesia (TEA) in cardiac surgery provides stable hemodynamics and postoperative analgesia by reducing stress response. The aim of this study was to investigate the effects of TEA in coronary artery bypass grafting (CABG) on postoperative pain, myocardial protection, intensive care unit (ICU) and hospital length of stay. Methods: After receiving approval from the hospital scientific committee and obtaining written informed consent from the participants, 40 patients, who were undergoing elective CABG, were included in the study. The patients were prospectively randomized into two groups as TEA group (n=20) and control group (n=20). Epidural catheters were placed one day before surgery at the T5-T6 level, levobupivacaine 2 µg/mL and fentanyl 5 mL/hr infusions were initiated in the ICU. Control group received intravenous infusion of fentanyl 8 µg/kg/hr. Infusions continued for 24 hours in both groups. Results: Time to extubation was shorter, postoperative hypertension was less frequent and pain scores were lower in TEA group than in control group (p<0.01). There was no difference in length of stay in the ICU, CK-MB and troponin I levels between the groups, however, length of hospital stay was shorter in TEA group. Conclusion: TEA with levobupivakain in CABG was found to provide stable hemodynamics, effective analgesia and to shorten length of hospital stay. (The Medical Bulletin of Haseki 2015; 53: 72-6)